Impact of Climate Policy on the Basque Economy - Mikel González; Rob Dellink (Fondazione Eni Enrico Mattei (FEEM), 2005)
In this paper we analyze the economic effects of CO2 emission reductions in the Basque Country (Spain) using an applied general equilibrium (AGE) model with specific attention to environment-energy-economy interactions. Environmental policy is implemented through a system of tradable pollution permits that the government auctions. The costs of different levels of CO2 abatement are discussed, focusing on the variations of macroeconomic, sectoral and environment-energy variables. Results show that the costs for achieving the Kyoto targets can remain limited if the appropriate combination of changes in fuel-mix and restructuring of the economy is induced.
Keywords: D58; H21; Q20; Q48; 330; Applied general equilibrium; Climate change; Tradable pollution permits; Basque country